Determinan Kejadian Ispa pada Balita di Wilayah Kerja Puskesmas Eahun Kabupaten Rote Ndao Tahun 2024 - Indri Ayu Sollo; Masrida Sinaga; Eryc Z. Haba Bunga (Yayasan Literasi Sains Indonesia, 2024)
Acute Respiratory Infection (ARI) is one of the health problems that needs serious attention, especially for toddlers who are very susceptible to infection with this disease because the toddler's immune system has not been optimally formed. This study aims to determine the factors related to the incidence of ARI in toddlers in the Eahun Health Center work area, Rote Ndao Regency. This type of research uses a quantitative design with a Case Control approach. The population in this study were all toddlers in the Eahun Health Center work area, totaling 1,856 toddlers, while the sample was 102 toddlers divided into 51 case samples and 51 control samples, the sampling technique was simple random sampling. The results of the study showed that factors related to the incidence of ARI in toddlers were nutritional status of toddlers (p=0.010; OR=3.100; 95%CI: 1.380-6.964), smoking habits of family members (p=0.017; OR=3.267; 95%CI: 1.314-8.121), residential density (p=0.009; OR=3.164; 95%CI: 1.396-7.172), and ventilation area (p=0.014; OR=3.040; 95%CI: 1.318-7.010), while the use of mosquito coils was not related to the incidence of ARI in toddlers (p=0.300). So it can be concluded that there is a relationship between nutritional status of toddlers, smoking habits of family members, residential density, and ventilation area with the incidence of ARI in toddlers in the Eahun Health Center work area.